Silibinin attenuates oxidative metabolism and cytokine production by monocytes from preeclamptic women. - Cristofalo, R.; Bannwart-Castro, C. F.; Magalhães, C. G.; Borges, V. T.; Peraçoli, José Carlos [UNESP]; Witkin, S. S.; Peraçoli, M. T. (Taylor & Francis, 2013)
Silibinin is a polyphenolic plant flavonoid with anti-inflammatory properties. The present study investigated the effect of silibinin on oxidative metabolism and cytokine production - tumor necrosis factor-alpha (TNF-α), interleukin (IL)12, granulocyte-macrophage colony-stimulating factor (GM-CSF), IL-6, IL-10, and transforming growth factor beta (TGF-β1) - by peripheral blood monocytes (PBM) from preeclamptic pregnant women. It is a case-controlled study involving women with preeclampsia (PE, n = 30) compared with normotensive pregnant (NT, n = 30) and with non-pregnant (NP, n = 30) women. Monocytes were obtained and cultured with or without silibinin (5 μM or 50 μM) for 18 h. Superoxide anion (O2-) and hydrogen peroxide (H2O2) release were determined by specific assays, and cytokine levels were determined by immunoenzymatic assays (ELISA). Monocytes from preeclamptic women cultured without stimulus released higher levels of O22, H2O2 and TNF-α, and lower levels of IL-10 and TGF-β1 than did monocytes from NT and NP women. Treatment in vitro with silibinin significantly inhibited spontaneous O2- and H2O2 release and TNF-α production by monocytes from preeclamptic women. The main effect of silibinin was obtained at 50 μM concentration. Thus, silibinin exerts anti-oxidative and anti-inflammatory effects on monocytes from preeclamptic pregnant women by inhibiting the in vitro endogenous release of reactive oxygen species and TNF-α production.
Keywords: antiinflammatory agent; antioxidant; cytokine; hydrogen peroxide; interleukin 10; interleukin 6; silibinin; silymarin; superoxide; transforming growth factor beta1; tumor necrosis factor alpha; blood; cell culture; cytology; drug effect; female; human; metabolism; monocyte; oxidative stress; preeclampsia; pregnancy; signal transduction; Anti-Inflammatory Agents; Antioxidants; Cells, Cultured; Cytokines; Female; Humans; Hydrogen Peroxide; Interleukin-10; Interleukin-6; Monocytes; Oxidative Stress; Pre-Eclampsia; Pregnancy; Signal Transduction; Silymarin; Superoxides; Transforming Growth Factor beta1; Tumor Necrosis Factor-alpha